ANALISIS USAHATANI TUMPANG SARI CABAI DAN TOMAT TERHADAP PENDAPATAN PETANI DI DESA LADOGAHAR, KECAMATAN NITA, KABUPATEN SIKKA - Gabriel Otan Apelabi; Oktaviana Rosario Sere Gili (Agriculture - Jurnal Ilmu Pertanian, 2023)
This study aims to analyze the income level of farmers who implement an intercropping system of chili and tomato in Ladogahar Village, Nita District, Sikka Regency, and to examine the internal and external factors influencing farm income. In addition, this study evaluates the efficiency of the intercropping system in improving productivity and farmers’ profits. The research used a case study method by directly observing field conditions and conducting interviews with farmers. The sampling technique applied was saturated sampling, in which the entire population was used as the research sample. The results show that the chili and tomato intercropping farming system in Ladogahar Village provides relatively high profits for farmers. The average total production cost incurred in this farming system is Rp 21,075,000 per planting season, while the average revenue obtained reaches Rp 61,200,000 per planting season. Thus, the average income earned by farmers from this intercropping system is Rp 40,125,000 per planting season, which is derived from the difference between total revenue and total production costs during the cultivation process. Based on the feasibility analysis, the chili and tomato intercropping farming system practiced in Erik Fram, Ladogahar Village, is considered feasible to develop. This is indicated by the R/C Ratio value of 2.90, meaning that every Rp 1 of production cost generates Rp 2.90 in revenue. Furthermore, the B/C Ratio value of 1.89 indicates that the profit obtained is greater than the total costs incurred. Therefore, the chili and tomato intercropping farming system has promising prospects and can provide significant economic benefits for farmers.